2018
DOI: 10.1111/jmi.12697
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the topographic characteristics and electrical charge distributions among Babesia‐infected erythrocytes and extraerythrocytic merozoites using AFM

Abstract: Tick-borne Babesia parasites are responsible for costly diseases worldwide. Improved control and prevention tools are urgently needed, but development of such tools is limited by numerous gaps in knowledge of the parasite-host relationships. We hereby used atomic force microscopy (AFM) and frequency-modulated Kelvin probe potential microscopy (FM-KPFM) techniques to compare size, texture, roughness and surface potential of normal and infected Babesia bovis, B. bigemina and B. caballi erythrocytes to better und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…4; see also Movie S14 at https://figshare.com/ s/8ba6afd9e161899d682c). Our results definitely indicated that multiparasite stages initially originated from a single trophozoite, confirming that the polyparasitism phenomenon is due to continuous rounds of multiplication (17,18) rather than to multiple infections of the same RBC.…”
Section: Discussionsupporting
confidence: 73%
“…4; see also Movie S14 at https://figshare.com/ s/8ba6afd9e161899d682c). Our results definitely indicated that multiparasite stages initially originated from a single trophozoite, confirming that the polyparasitism phenomenon is due to continuous rounds of multiplication (17,18) rather than to multiple infections of the same RBC.…”
Section: Discussionsupporting
confidence: 73%
“…This time was also comparable to the time required for the paired-pyriforms when developed through a synchronized budding to tetrads (Table 1). Our results definitely indicated that multiparasite stages initially originated from a single trophozoite, confirming that the polyparasitism phenomenon is due to continuous rounds of multiplication (17,18) rather than multiple infections of the same RBC.…”
Section: The Paired-pyriform Dominates the Asexual Cycle Of B Divergenssupporting
confidence: 73%
“…Free merozoites were not observed to invade cells that were already parasitized. This phenomenon has been associated recently with a possible electrical mechanism of repulsion that could prevent free Babesia merozoites from interacting with already infected erythrocytes 20 . This fact also suggests that the polyparasitism observed in multiple parasites stages probably results from continuous cycles of division from an original invading parasite rather than by multiple infections of the same erythrocyte.…”
Section: Discussionmentioning
confidence: 97%